Jim Crow in the Asylum - Smith, Kylie M. (The University of North Carolina Press, 2026)
There is a complicated history of racism and psychiatric healthcare in the Deep South states of Georgia, Alabama, and Mississippi. The asylums of the Jim Crow era employed African American men and women; served as places of treatment and care for African Americans with psychiatric illnesses; and, inevitably, were places of social control. Black people who lived and worked in these facilities needed to negotiate complex relationships of racism with their own notions of community, mental health, and healing. Kylie M. Smith mixes exhaustive archival research, interviews, and policy analysis to offer a comprehensive look at how racism affected Black Southerners with mental illness during the Jim Crow era. Complicated legal, political, and medical changes in the late twentieth century turned mental health services into a battlefield between political ideology and psychiatric treatment approaches, with the fallout having long-term consequences for patient outcomes. Smith argues that patterns of racially motivated abuse and neglect of mentally ill African Americans took shape during this era and continue to the present day. As the mentally ill become increasingly incarcerated,Jim Crow in the Asylum reminds readers that, for many Black Southerners, having a mental illness was and still tantamount to committing a crime.